Relatos míticos y prácticas rituales en Pachacamac - Peter Eeckhout (Bulletin de l'Institut Français d'Études Andines, 2004)
In this paper, I provide a critical synthesis of current information and knowledge related to the cult of Ychsma, an important deity whose sanctuary was established in the monumental precinct of Pachacamac, central coast of Peru. This analysis uses ethnohistoric and ethnographic records, as well as new archaeological data collected during research recently carried out at the site and surrounding area. Etymology and the study of written sources underlines the coastal characteristics of this deity. They also show that the cult and the myths were manipulated by the Inkas. A series of ritual practices (human and animal sacrifices, offerings, pilgrimage, divination, ancestor cults) are examined in the light of both colonial accounts (mainly extirpations of idolatries) and archaeological finds. Such a systematic comparison enables me to draw a more complete picture of prehispanic religious customs than anything previously proposed for the Lurín-Rímac area.